2018
DOI: 10.1136/bcr-2017-222158
|View full text |Cite
|
Sign up to set email alerts
|

SLE presenting as demyelinative autoimmune visual loss

Abstract: A healthy 38-year-old woman developed sudden unilateral vision loss due to retrobulbar optic neuritis in the wake of varicella-zoster virus infection. She had no further central nervous system (CNS) lesions. Antinuclear antibodies (ANA) and anti-aquaporin 4 antibodies were found, consistent with neuromyelitis optica (NMO). Later, serial MRIs showed dynamic short-segment and long-segment myelitis lesions, ANA titre increased and additional autoantibodies were found including anti-dsDNA, anti-chromatin/nucleosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…5,6 We further identified four more cases in the literature where NMOSD was the first manifestation of SLE. 710 The salient features of these six cases where NMOSD was the first manifestation of SLE are summarized in Table 1. All these six patients were women, all fulfilled the clinical and imaging criteria for NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 We further identified four more cases in the literature where NMOSD was the first manifestation of SLE. 710 The salient features of these six cases where NMOSD was the first manifestation of SLE are summarized in Table 1. All these six patients were women, all fulfilled the clinical and imaging criteria for NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of thyroid eye disease manifest in patients with hyperthyroidism. However, thyroid eye disease can also manifest in individuals with a thyroid status other than hyperthyroidism, although the incidence rate was found to be low (10%) (Schattner et al 2023). In a separate study conducted by Muñoz-Ortiz et al (2020), the majority of thyroid eye disease patients were found to have hyperthyroidism (86.2%).…”
Section: Correlation Between Thyroid Status and Clinical Activity Scorementioning
confidence: 98%